The Psychology of Extremism in of Economic Crisis: A Dual-Perspective Study of 2025 Trade War - Zora Sukabdi; Eri R. Hidayat; Umi Muzayanah (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
Trade wars, while motivated by economic goals, had consequences that transcended the economic realm, impacting social and political domains. This study employs a qualitative research design to investigate the relationship between the 2025 trade war and the potential emergence of violent extremism by interviewing two pivotal groups: former terrorist offenders, who provide insider insights, and terrorism analysts, who present outsider perspectives on extremist organizations. The results indicate that modern extremists can be classified by ideology, scope, generational cohort, and behavioral tendencies. The study emphasizes that global economic instability, resulting in local crises, can intensify extremism and criminal activity, especially in vulnerable groups. This study categorizes extremists into three classes based on their reactions to economic crises: “deradicalized,” “exploiters,” and “vulnerable.”